Evaluation of relationship among polycystic ovary syndrome, atherogenic index of plasma, and high sensitive C reactive protein - Bozkurt, Erhan; Beysel, Selvihan; Vurmaz, Ayhan; Atay, Emre; Gokaslan, Serkan; Ertekin, Ayse (Annals of Medical Research, 2021)
Aim: In this study, we aimed to investigate the relationship among cardiovascular risk factors (CRFs), atherogenic index of plasma (AIP) and high-sensitivity C-reactive protein (hs-CRP) levels in polycystic ovary syndrome (PCOS) patients and identify risks earlier. Materials and Methods: 131 patients diagnosed with PCOS according to Rotterdam criteria and 140 healthy controls were included from August 2019 to October 2019. Blood samples were done in the early follicular phase of the patients and were done after 10-12 hours of fasting.Results: AIP and hs-CRP levels were higher in PCOS group (p0.001, p0.001, respectively). In PCOS group significantly positive correlation was determined between CRFs and AIP. Significantly positive correlation was determined only between hs-CRP and triglyceride levels (r=0.280, p0.05). In PCOS group, there was a significantly positive correlation between hs-CRP levels and AIP (r=0.372, p0.001).Conclusion: AIP and hs-CRP may be beneficial markers for early monitoring of cardiovascular diseases in PCOS patients.